Upper Extremity Pulse Pressure Predicts Amputation-Free Survival after Lower Extremity Bypass. Issue 7 (July 2017) - Wise, Eric S.; Wergin, Justine E.; Mace, Eric H.; Kallos, Justiss A.; Muhlestein, Whitney E.; Shelburne, Nicholas J.; Hocking, Kyle M.; Brophy, Colleen M.; Guzman, Raul J.
Increased pulse pressure reflects pathologic arterial stiffening and predicts cardiovascular events and mortality. The effect of pulse pressure on outcomes in lower extremity bypass patients remains unknown. We thus investigated whether preoperative pulse pressure could predict amputation-free survival in patients undergoing lower extremity bypass for atherosclerotic occlusive disease. An institutional database identified 240 included patients undergoing lower extremity bypass from 2005 to 2014. Preoperative demographics, cardiovascular risk factors, operative factors, and systolic and diastolic blood pressures were recorded, and compared between patients with pulse pressures above and below 80 mm Hg. Factors were analyzed in bi- and multivariable models to assess independent predictors of amputation-free survival. Kaplan-Meier analysis was performed to evaluate the temporal effect of pulse pressure ≥80 mm Hg on amputation-free survival. Patients with a pulse pressure ≥80 mm Hg were older, male, and had higher systolic and lower diastolic pressures. Patients with pulse pressure <80 mm Hg demonstrated a survival advantage on Kaplan-Meier analysis at six months (log-rank P = 0.003) and one year (P = 0.005) postoperatively. In multivariable analysis, independent risk factors for decreased amputation-free survival at six months included nonwhite race, tissue loss, infrapopliteal target, and preoperative pulse pressure ≥80 mm Hg (hazard ratio 2.60; P = 0.02), while only tissue loss and pulse pressure ≥80 mm Hg (hazard ratio 2.30, P = 0.02) remained predictive at one year. Increased pulse pressure is independently associated with decreased amputation-free survival in patients undergoing lower extremity bypass. Further efforts to understand the relationship between increased arterial stiffness and poor outcomes in these patients are needed.